La innovación en educación superior a través de las comunidades de práctica -CoP- - Galván, María Guadalupe; Ibarra, Luis Jesús; Flores, Victor Guillermo (My University, 2019)
The present work is a partial report of investigation, whose objective is to stimulate the culture of the learning between Academic Bodies of diverse institutions, same that develop competences for the innovation in Higher Education. A strategy focused on the formation of the Community of Practice (CoP) among the academic bodies of the Guanajuato Node has been privileged, which has allowed to account for the improvement of student learning with the support of information technologies. The project was approved by the Secretariat of Public Education (SEP) and the innovation of the practices has been carried out through action research and with a theoretical foundation based on the studies of complex thinking, the critical use of tics and theories of innovation. As part of some conclusions to which it has been bequeathed, there are the following: a) Innovating educational practices implies an irrevocable epistemological assumption that underlies all educational vision. b) In higher education practices, it is necessary to generate the training conditions for teachers to appropriate and integrate information and communication technologies.
El presente trabajo es un informe parcial de investigación, cuyo objetivo es incentivar la cultura del aprendizaje entre Cuerpos Académicos de diversas instituciones, mismas que desarrollan competencias para la innovación en Educación Superior. Se ha privilegiado una estrategia centrada en la conformación de la Comunidad de Práctica (CoP) entre los cuerpos académicos del Nodo Guanajuato, que han permitido dar cuenta de la mejora de los aprendizajes de los estudiantes con el apoyo de las tecnologías de la información. El proyecto fue aprobado por la Secretaría de Educación Pública (SEP) y la innovación de las prácticas se ha realizado a través de la Investigación-acción y con una fundamentación teórica basada en los estudios del pensamiento complejo, el uso crítico de las tic y las teorías de la innovación. Como parte de algunas conclusiones a las que se ha llegado, se tienen las siguientes: a) Innovar las prácticas educativas, implica un supuesto epistemológico irrenunciable que subyace a toda visión educativa. b) En las prácticas de educación superior, se requiere generar las condiciones formativas para que los profesores se apropien e integren las tecnologías de la información y la comunicación.
Keywords: EDUCACIÓN SUPERIOR; COMUNIDADES DE PRÁCTICA; INNOVACIÓN; PRÁCTICAS DOCENTES